A comprehensive in-depth study of tri-state inverter based DCO. (May 2020) - Terosiet, M.; Zianbetov, E.; Vallette, F.; Louerat, M.M.; Garda, P.; Galayko, D.; Feruglio, S.
Abstract: This paper proposes an in-depth analysis of the tri-state inverter based digitally controlled oscillator. This oscillator topology has been reported in numerous publication, however its features remain poorly understood. In this study, we propose to focus on these lacks. We specifically addressed the oscillation period and the associated jitter as these quantities are the design key parameters. In this paper, we propose analytical expressions taking into consideration the design, the technology as well as the input code. These equations are suitable for hand calculations and have helped to establish a design methodology for rapid implementation. Two circuits have been designed in STMicroelectronics CMOS 65 nm process. The first one was evaluated through simulations. Then, the measurement results obtained with the second circuit manufactured within the same technology node are presented. Finally, the experimental data support the proposed theory.